Straightforward sustainable synthesis of novel non-endocrine disruptive bio-based organic UV-B filters with antimicrobial activity - Matthieu M. Mention; Cédric Peyrot; Blandine Godon; Jimmy Alarcan; Fanny Brunissen; Marina Grimaldi; Patrick Balaguer; Albert Braeuning; Florent Allais (Green Chemistry Letters and Reviews, 2023)
ABSTRACTWith an increasing demand for safe and natural products from both industries and consumers, paired with the recent ban of decried molecules (i.e. octinoxate, avobenzone or octocrylene) due to their high negative impact on humans and the environment (i.e. endocrine disruption, coral bleaching), safe bio-based alternatives are a necessary and promising surrogate to substitute current commercialized petroleum-based UV filters. In this context, a class of bio-based molecules, displaying interesting UV-B filtering properties and great photostability were developed from furfural and 5-hydroxymethylfurfural (HMF), using the Knoevenagel condensation with a set of green conditions to minimize the impact on environment. Furthermore, those furfural- and HMF-based molecules demonstrated antimicrobial properties as secondary activity, highly sought by industries. Some furan derivatives being recognized to exhibit toxicological risks, in silico and in vitro assays were conducted and demonstrated the absence of endocrine disruption activity for these new molecules.